2014
DOI: 10.1021/pr500434s
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolite Profiles of the Obese Population Are Gender-Dependent

Abstract: Recent studies have identified that several amino acids, in particular, branched-chain amino acids (BCAAs), increased significantly in obese compared with lean individuals. Additionally, these metabolites were strongly associated with future diabetes, rendering them prognostic markers suitable for obese populations. Here we report a metabonomic study that reveals new findings on the role of these amino acid markers, particularly BCAAs, in a Chinese cohort including 106 healthy obese and 105 healthy lean partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 56 publications
10
55
0
Order By: Relevance
“…However, this positive association was only found in women ( r = 0.354, P = 0.016), which did not reach statistical significance in men ( r = 0.245, P = 0.094), while, in a study on 685 participants, Lee et al [20] found that men had higher level of BCAA as well as BMI, waist-hip ratio, IR, and dietary energy intake compared with women. The gender-dependence was also reported by Xie et al [30]. They presented that BCAA was correlated with IR only in obese Chinese men; similar results were validated by another two cohorts on Chinese and Americans.…”
Section: Resultssupporting
confidence: 84%
“…However, this positive association was only found in women ( r = 0.354, P = 0.016), which did not reach statistical significance in men ( r = 0.245, P = 0.094), while, in a study on 685 participants, Lee et al [20] found that men had higher level of BCAA as well as BMI, waist-hip ratio, IR, and dietary energy intake compared with women. The gender-dependence was also reported by Xie et al [30]. They presented that BCAA was correlated with IR only in obese Chinese men; similar results were validated by another two cohorts on Chinese and Americans.…”
Section: Resultssupporting
confidence: 84%
“…11,12,42 As described above, we further detected a number of RNA-, protein-, and metabolite-based biomarker candidates. In particular, we observed up regulation of HFD responsive proteins of TCA cycle and OXPHOS such as SDHB and SUCLG1 in WAT and down regulation of HFD responsive proteins involved in vitamin B metabolism such as PDXDC1 and DHFR in liver.…”
Section: ■ Conclusion and Outlookmentioning
confidence: 99%
“…Our recent serum metabonomic study on healthy lean and obese subjects showed that the serum metabolite profiles including several BAs (glycolithocholic acid and 12α-hydroxy-3-oxocholadienic acid) of the obese population are gender-dependent. 20 The gender differences in BAs may result in gender-dependent responses to some therapeutic drugs, as several basolateral membrane proteins (such as MRP2, MRP3, and MRP4) that transport BA are also key drug transporters. For example, the total BA concentration was significantly reduced only in men (−18.6%), whereas it remained almost unchanged in women (+0.36%) after fenofibrate, a hypolipidaemic drug, treatment.…”
Section: Discussionmentioning
confidence: 99%